Initial Clinical Results and In Vitro Testing of the New CGuard MicroNet-Covered "One-Size-Fits-All" Carotid Stent. (August 2019) - Wissgott, Christian; Brandt-Wunderlich, Christoph; Kopetsch, Christoph; Schmidt, Wolfram; Andresen, Reimer
Purpose: To evaluate a MicroNet-covered stent designed for the carotid artery with the new ability to adjust to different vessel diameters.Materials and Methods: Thirty consecutive patients (mean age 72.1±7.7 years; 26 men) with symptomatic stenosis (86.3%±6.4%) of the internal carotid artery were treated with the new self-adjusting nitinol stent, which has a self-expanding, open-cell design covered by an outer conformable layer (MicroNet). The only stent used was the "One-Size-Fits-All" CGuard stent with lengths of 30 or 40 mm. In bench testing, the chronic outward force of the One-Size-Fits-All stent was determined with a segmented head radial force test device. The stent was deployed directly into the test device at a diameter of 5.0 mm, and the chronic outward force was measured up to 10.0 mm, the maximum expansion of the stent.Results: The stent was successfully implanted in all 30 patients without periprocedural complications, including no neurological events within 30 days. The chronic outward force normalized by stent length demonstrated a near-equivalent radial force outcome: The stent displayed only a minor difference between the minimal radial force at 9.0 mm (0.195 N/mm) and the maximal radial force at 5.5 mm (0.330 N/mm).Conclusion: The new self-adjusting, MicroNet-covered stent has high conformability combined with an almost equivalent radial force at expansion diameters ranging from 5.5 to 9.0 mm. The first clinical results demonstrate that the new One-Size-Fits-All stent can be safely implanted in internal carotid arteries with reference diameters within this range.